2022
DOI: 10.1262/jrd.2022-061
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of interferon-tau research and potential direction beyond pregnancy recognition

Abstract: Since the discovery of interferon-tau (IFNT) over 30 years ago as the trophectodermal cytokine responsible for the maintenance of the maternal corpus luteum (CL) in ruminants, exhaustive studies have been conducted to identify genes and gene products related to CL maintenance.Recent studies have provided evidence that although CL maintenance, with the up-and downregulation of IFNT, is important, its regulatory role in the endometrial expression of interferonstimulated genes (ISGs) is far more important for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…Given results from NCT data, there is a high number of reasons to believe that lowdose type IFN I and III IFN based nasal sprays could match the definition of a therapeutic vaccine with beneficial effects than prophylactic ones.Therefore, whilst potential vaccine candidates can prevent severe cases of COVID-19 disease, it would have the highest impact when administered in varying populations of vulnerable people potentially with or without comorbidities who became infected and developed symptoms that would be noticeable . Examining further the administration of type I IFN from NCTs clarifies that IFN alpha-2b, epsilon, omega and perhaps IFN beta1, (BAI et al, 2022) and type III (IFN lambda1, lambda2 and lambda3) may act as mimitics of cellular infection and stimulate a robust and natural immune response against either viral or neoplastic pathologies, and likewise, such an intervention fits the definition of a traditional vaccine. Because this likely requires further research into dosages, we might refer to the potential immunization process as a long-term one.…”
Section: Discussionmentioning
confidence: 99%
“…Given results from NCT data, there is a high number of reasons to believe that lowdose type IFN I and III IFN based nasal sprays could match the definition of a therapeutic vaccine with beneficial effects than prophylactic ones.Therefore, whilst potential vaccine candidates can prevent severe cases of COVID-19 disease, it would have the highest impact when administered in varying populations of vulnerable people potentially with or without comorbidities who became infected and developed symptoms that would be noticeable . Examining further the administration of type I IFN from NCTs clarifies that IFN alpha-2b, epsilon, omega and perhaps IFN beta1, (BAI et al, 2022) and type III (IFN lambda1, lambda2 and lambda3) may act as mimitics of cellular infection and stimulate a robust and natural immune response against either viral or neoplastic pathologies, and likewise, such an intervention fits the definition of a traditional vaccine. Because this likely requires further research into dosages, we might refer to the potential immunization process as a long-term one.…”
Section: Discussionmentioning
confidence: 99%
“…On gestational days 14-15 in cattle, the elongating conceptus begins to produce a major cytokine, IFNT, which peaks on day 19 and declines soon after the conceptus attaches to the uterine epithelium. IFNT, a pregnancy recognition protein, acts on the expression of elongation-and implantation-related genes in the endometrium and abrogates luteolytic mechanisms, leading to continued P4 production [27,28]. Recent studies on ovine and bovine EVs have shown that uterine EVs contained IFNT [20,29,30] and upregulated the expression of several IFNT-stimulated genes (ISGs), such as ISG15, MX1, MX2, STAT1, and STAT2 in EECs during the peri-attachment period [20,30].…”
Section: Discussionmentioning
confidence: 99%
“…The IFNT, which is present at low levels in extrauterine tissues as well as the peripheral circulation, signals the maternal recognition of bovine pregnancy (Szenci, 2021). IFNT helps maintain the corpus luteum function and regulates the maternal immune system to ensure embryo implantation (Bai et al, 2022;Martal et al, 1990;Talukder et al, 2017). IFNT has been shown to act in a paracrine manner on the endometrium by inhibiting the secretion of prostaglandin F2α (PGF2α), which prevents the lysis of the corpus luteum, ensuring that the ovarian corpus luteum continues to produce progesterone (Spencer et al, 2007;Wiltbank et al, 2023).…”
Section: Ifnt and Isg Smentioning
confidence: 99%